STRATEGY DIGITAL MARKETING AND SUCCESS IN FARMING PLANT CACTUS AND PEPEROMIA AT PT. GRAHA MITRATAMA INNOVASI - Tirta Yoga; Eri Yusnita Arvianti; Dyanasari Dyanasari (Jurnal Hexagro, 2024)
This research discussed the implementation of digital marketing in cultivating cacti and peperomia plants and its impact on business success. Digital marketing has become essential in promoting cacti and peperomia plants through digital platforms. The research methodology employed in this study includes surveys, interviews, statistical data analysis, case studies, and content observation and analysis. The research findings indicate that digital marketing can enhance brand awareness by creating websites, blogs, and social media platforms that provide comprehensive information about cacti and peperomia plants. Additionally, paid advertising strategies on social media and search engines enable precise market targeting and improve advertising expenditure efficiency. Implementing digital marketing also contributes to the increase in online sales through online stores or marketplaces. Discount and particular promotion strategies prove to be effective in attracting buyer interest and driving conversions. By leveraging SEO strategies, monitoring customer reviews, providing educational content, and using features like live streaming and webinars, cacti and peperomia plant cultivation can successfully implement digital marketing.